Anti-transforming growth factor ß antibody treatment rescues bone loss and prevents breast cancer metastasis to bone. - Biswas, S; Nyman, J; Alvarez, J; Chakrabarti, A; Ayres, A; Sterling, J; Edwards, J; Rana, T; Johnson, R; Perrien, D; Lonning, S; Shyr, Y; et al. (2011)
Breast cancer often metastasizes to bone causing osteolytic bone resorption which releases active TGFβ. Because TGFβ favors progression of breast cancer metastasis to bone, we hypothesized that treatment using anti-TGFβ antibody may reduce tumor burden and rescue tumor-associated bone loss in metastatic breast cancer. In this study we have tested the efficacy of an anti-TGFβ antibody 1D11 preventing breast cancer bone metastasis. We have used two preclinical breast cancer bone metastasis models, in which either human breast cancer cells or murine mammary tumor cells were injected in host mice via left cardiac ventricle. Using several in vivo, in vitro and ex vivo assays, we have demonstrated that anti-TGFβ antibody treatment have significantly reduced tumor burden in the bone along with a statistically significant threefold reduction in osteolytic lesion number and tenfold reduction in osteolytic lesion area. A decrease in osteoclast numbers (p = 0.027) in vivo and osteoclastogenesis ex vivo were also observed. Most importantly, in tumor-bearing mice, anti-TGFβ treatment resulted in a twofold increase in bone volume (p<0.01). In addition, treatment with anti-TGFβ antibody increased the mineral-to-collagen ratio in vivo, a reflection of improved tissue level properties. Moreover, anti-TGFβ antibody directly increased mineralized matrix formation in calverial osteoblast (p = 0.005), suggesting a direct beneficial role of anti-TGFβ antibody treatment on osteoblasts. Data presented here demonstrate that anti-TGFβ treatment may offer a novel therapeutic option for tumor-induced bone disease and has the dual potential for simultaneously decreasing tumor burden and rescue bone loss in breast cancer to bone metastases. This approach of intervention has the potential to reduce skeletal related events (SREs) in breast cancer survivors.